La nuit chez les Inuit canadiens du haut Arctique : une nuit véritable, mais en trompe-l’œil - Guy Bordin (Bollettino della Società Geografica Italiana, 2019)
For many observers, night in high latitudes can be summed up schematically as the seasonal astronomical phenomenon called “arctic night” and its spectacular alternation with its counterpoint, the so-called “midnight sun”. But what about the day-to-day night of people living in these regions? What are the relations they establish between the seasonal “dark-light” cycles and the circadian “night-day” cycles? In this article, we will see how the northern Inuit in the eastern Canadian Arctic combine these two dimensions to produce a concept of night whose essence lies elsewhere than in the sole darkness.